Trypanosoma cruzi Secreted Cyclophilin TcCyP19 as an Early Marker for Trypanocidal Treatment Efficiency - Perrone, Alina Elizabeth (2023)
Cyclophilins (CyPs) are a family of enzymes involved in protein folding. Trypanosoma cruzi, the causative agent of Chagas disease, has a 19-kDa cyclophilin, TcCyP19, that was found to be secreted in parasite stages of the CL Brener clone and recognized by sera from T. cruzi-infected mice and patients. The levels of specific antibodies against TcCyP19 in T. cruzi-infected mice and subjects before and after drug treatment were measured by an in-house enzyme linked immunosorbent assay (ELISA). Mice in the acute and chronic phase of infection, with successful trypanocidal treatments, showed significantly lower anti-TcCyP19 antibody levels than untreated mice. In children and adults chronically infected with T. cruzi, a significant decrease in the anti-TcCyP19 titers was observed after 12 months of etiological treatment. This decrease was maintained in adult chronic patients followed-up 30–38 months post-treatment. These results encourage further studies on TcCyP19 as an early biomarker of trypanocidal treatment efficiency.